Human Capital and Search–Based Discovery: A Study of High–Tech Entrepreneurship - Marvel, Matthew R. (Entrepreneurship Theory and Practice, 2013)
What types of knowledge and experience enable those who have the desire to start a venture find an appropriate opportunity? To respond to this question, a human capital perspective is used with a sample of 166 founders of new technology ventures in university incubators. General human capital is assessed using experience depth and formal education. Specific human capital is measured using prior start–up experience as well as Shane's knowledge framework of markets, customer problems, and ways to serve markets. Findings reveal key aspects of human capital vital to explaining search–based discovery. Implications for research and entrepreneurship education are drawn.